A review on the potential healing effects of citrus peel extracts in wound therapy - G. Sridevi; S. Srividya; V. M. Bhavani; R. Hemalatha; V. Rajalaxmi (SRM Journal of Research in Dental Sciences)
Background: A wound is an alteration to the skin and the soft tissue caused by damage produced by physical, chemical, or infective injuries. Three crucial, complex physiological processes – proliferation, remodeling, and inflammation – are involved in the healing of wounds. Infections, immunosuppression, and poor circulation can all impede these normal processes, resulting in delayed healing and increasing the risk of a chronic wound with underlying medical conditions. Several edible, inedible plants and plant derivatives were employed as standard herbs for wound healing in Ayurveda. Materials and Methods: Review of literature was done of different sources or article published under scopus, web of science and pubmed indexing and also from book chapters from eminent publishers. Discussion: The ability of plants to heal wounds has been linked to the presence of bioactive components such as triterpenes, alkaloids, and biomolecules, which are prevalent in a variety of plant products. These phytoconstituents fix wounds and have an impact on one or more stages of the healing process. Fruits with citrus peels are great providers of Vitamin C. Peels are rich in potential components such as flavonoids, Vitamin C, carotenoids, dietary fibers, and essential oils. Beneficiary flavone glycosides, hydroxylated pro-methoxy flavones (hydroxylated PMFs), methylated flavonoids, proanthocyanidins, and dihydrochalcones are all present in these peels. Conclusion: Thus, citrus peel extracts can effectively reduce wound surface area and enhance muscle tensile strength, coupled with their antibacterial, fungal, anti-inflammatory, antioxidant, and antidiabetic properties that expedite the healing process.